Design buck converter for 12VDC to 6VDC - Mohd Safarizal Yaakob (School of Electrical System Engineering, University Malaysia Perlis, 2011)
A switched mode power supply (SMPS) or switching regulator, efficiently converters a DC voltage level to another DC voltage level, via an intermediate magnetic (inductor) storage or transfer stage, such that a continuous, possibly constant, load current flows, usually at power levels below a few kilowatts. DC-DC Converters are needed because unlike AC, DC cant simply be stepped up or down using a transformer.